Demographic, Reproductive, and Medical Risk Factors for Intrauterine Device Expulsion. Issue 4 (April 2023) - Anthony, Mary S.; Zhou, Xiaolei; Schoendorf, Juliane; Reed, Susan D.; Getahun, Darios; Armstrong, Mary Anne; Gatz, Jennifer; Peipert, Jeffrey F.; Raine-Bennett, Tina; Fassett, Michael J.; Saltus, Catherine W.; Ritchey, Mary E.; et al.
ABSTRACT: Intrauterine device (IUD) expulsion is more common among women with heavy menstrual bleeding, parity, higher body mass index (BMI), younger age, dysmenorrhea, or immediate postabortion or postpartum insertion. The APEX-IUD study was an observational cohort study of 326, 658 individuals examining the association with breastfeeding, IUD type, and timing of postpartum IUD insertion with IUD expulsion and uterine perforation. This data set provides an opportunity to examine specific demographic, reproductive, and medical risk factors associated with IUD expulsion. This analysis of APEX-IUD data aimed to determine the associations of 6 risk factors (age, race/ethnicity, parity, BMI, heavy menstrual bleeding, and dysmenorrhea) and IUD expulsion, as well as the extent to which these associations differed for LNG-IUD compared with copper IUD users. Individuals aged 50 years or younger at the time of IUD insertion without a delivery 52 weeks or less before insertion were included. Individuals were followed from IUD insertion until IUD expulsion, uterine perforation, removal, reinsertion, expiration, pregnancy, hysterectomy, death, disenrollment from the health care system, or end of study period (June 2018). Crude incidence rates for each risk factor category were calculated using the number of expulsions during the time at risk divided by the total person-years at risk and were reported as the number of expulsions per 1000 person-years at risk. Hazards ratios (HRs) and 95% confidence intervals from Cox regression models were used to evaluate associations of the risk factors with IUD expulsion. These models were adjusted for potential confounding effects and were separately used to assess the association of covariates with IUD expulsion varied by IUD type. The total study cohort included 228, 834 individuals (LNG-IUD: 184, 733 [80.7%]; copper IUD: 41, 123 [18.0%]; unknown type: 2978 [1/3%]). The average length of follow-up was 2.0 years, and there were 6762 expulsions with a crude incidence rate of 14.9 per 1000 person-years (95% confidence interval, 14.6–15.3). Adjusted hazards ratios (aHRs) showed the younger age groups having a higher risk of IUD expulsion and a trend toward lower aHRs with increasing age. Individuals with parity of 4 or more had the highest risk of IUD expulsion, and a parity of 2 was associated with the lowest risk on adjusted analysis. Adjusted analysis revealed a greater risk of IUD expulsion among individuals with higher BMI or heavy menstrual bleeding diagnosis compared with the comparator group. Multiple racial and ethnic groups including non-Hispanic Black, Hispanic Black, Hispanic White, Asian, or Pacific Islander were associated with a greater risk of IUD expulsion compared with non-Hispanic Whites when adjusting for covariates. When comparing aHRs by copper IUD or LNG-IUD; younger age was more strongly associated with expulsion among copper IUD users than LNG-IUD users, the risk for expulsion associated with obesity was significantly attenuated for copper IUD users compared with LNG-IUD users, and the risk of expulsion for those with heavy menstrual bleeding was partially attenuated by copper IUDs. Adjusted analysis revealed no association between dysmenorrhea and IUD expulsion. The results of this study show that, among the 6 risk factors investigated here, the risk of IUD expulsion was highest among individuals with a diagnosis of heavy menstrual bleeding, particularly in recent and past periods.